A Review Study of Developing an Advertising Strategy for Westerner’s Companies among Middle East Countries: the Islamic Perspective - Behravan, Navid; ., Roozbeh Masoudi (Information Management and Business Review, 2012)
The burst in the number of commercial advertisement has been growing over the last few years. The western companies, obviously, have the most shares of market among the Middle Eastern. Hence, it is critical for the companies to adopt an applicable advertisement strategy for their market. The marketers must be aware of both cultural and religious values of the target customers in their advertisement strategy. In the other word, there are many ambiguities and challenges exist to discover such values among Middle East countries. This study aims to provide a guideline for the companies to plan appropriate advertisement strategy in Middle East countries. In-line with the research objective, the study explores standardization and localization advertisement strategy aligns with the Muslim countries’ advertisement strategy. The study also presents the importance of both regional culture and religion in advertising strategy in Muslim countries. As the paperâ€™s outcome, an Advertising Multi-Views Model has introduced to assist multi-national companies to develop their business among Middle East countries. The model advocates the higher ads effectiveness by supporting humor, fairness, morality and incentives in companiesâ€™ advertisement strategy.